Highly compact quad‐band bandpass filter with flexibly controllable passbands - Fan Zhang; Yang Gao; Yi Wang; Yi Zhang; Yuliang Dong; Jun Xu (Electronics Letters, 2021)
Abstract This letter reports a highly compact microstrip quad‐band bandpass filter based on two folded λ/4 stepped impedance resonators and three folded dual‐mode short stub‐loaded resonators. The two stepped impedance resonators not only form the first passband but also serve as the feed structure and provide the source‐load coupling path for the three higher passbands created by the short stub‐loaded resonators. Thus, a compact size can be obtained, and three pairs of transmission zeros can be realised near the three higher passbands to improve the frequency selectivity. It has been shown that the centre frequencies and bandwidths of the four passbands can be controlled independently. A microstrip quad‐band bandpass filter centred at 1.1/2.05/3/3.55 GHz is implemented and tested achieving an extremely small size of 0.07λg × 0.14λg, where λg is the guided wavelength at 1.1 GHz. This presents one of the smallest quad‐band bandpass filter ever demonstrated in the literature.